A Computational and Experimental Analysis of Aldehyde Photooxidation Driven by Visible Light in a Homemade Reactor - Cervantes-González, Javier; Mora-Rodríguez, Salma E.; Benitez-Puebla, Luis J.; López-Caamal, Fernando; García-Revilla, Marco A.; Vázquez, Miguel A.; Lagunas-Rivera, Selene (Synlett, 2023)
A computational and experimental analysis of HAT mechanism to obtain carboxylic acid via photooxidation of aldehyde is described, using a homemade reactor. The considered photocatalysts are organic dyes such as 2-chloroanthraquinone (2-ClAQN), rhodamine 6G (Rh6G), fluorescein (Fl), and eosin B (EOB); and the light spectrum is that of the visible light.
Keywords: photooxidation; organic dyes metals free; water; green chemistry; process HAT